Cationic thiazolothiazole derivatives – A new class of photosensitizing agents against Staphylococcus aureus - Cerqueira, Ana F.R. (2024)
The assessment of thiazolothiazoles (TzTz) as photosensitizers in photodynamic inactivation (PDI) experiments is reported for the first time. Mono and dicationic TzTz derivatives were synthesized, and their photosensitizing ability was assessed on Staphylococcus aureus cells, both in suspension or attached to a surface, and using white light. The biological results showed that the photodynamic efficiency of these derivatives is dependent on the TzTz structure and irradiation time. The best results were obtained with the monocationic derivative TPATzTzPyMeþthat allowed to reach a value over 7 log (99.9999 %) cell inactivation after white light irradiation for 30 min. Furthermore, TPATzTzPyMeþalso revealed to be effective on the inactivation of S. aureus adhered to surfaces, a good indication of its potential to prevent biofilm formation. TPATzTzPyMeþwas also effective against Escherichia coli, with a reduction in cell viability of 5.7 log after irradiation for 30 min.